Characteristics Of Treating Arabic Grammar In Educational Books For Russian Orientalists/ Ø®ØµØ§Ø¦Øµ Ù…Ø¹Ø§Ù„Ø¬Ø© Ø§Ù„Ù†ØÙˆ Ø§Ù„Ø¹Ø±Ø¨ÙŠ ÙÙŠ ÙƒØªØ¨ ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ù„Ù„Ù…Ø³ØªØ´Ø±Ù‚ÙŠÙ† Ø§Ù„Ø±ÙˆØ³ - YakÅŸi, Mukarama (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
This study aimed to identify the characteristics of grammatical rules treatment in educational books of Russian orientalists in teaching the Arabic language.Â Because of the rare study, this topic. This paper analyzes and evaluates one of the books of teaching Arabic grammar to non-Arabic speakers. It aims to reveal its different aspects in organizing and using grammatical rules, determining what is useful for them in teaching Arabic grammar to help in using the target language, and making some recommendations that contribute to this. The results are indicating that the book's treatment of grammatical rules is distinctly different. That follows the functional progression and focuses on the treatment of the similarities and differences between the grammatical of Arabic and Russian languages. Furthermore, it is interesting to provide how to use the rules, so that the learner can gradually form compound and straightforward sentences, which helps him use the target language.Â